Evaluation of the risk factors of pilonidal sinus: A single center experience - Shahram BOLANDPARVAZ; Parisa MOGHADAM DIZAJ; Roohollah SALAHI; Shahram PAYDAR; Mohammad BANANZADEH; Hamid-Reza ABBASI; Armaghan ESHRAGHIAN (Turkish Journal of Gastroenterology, 2019)
-